The Influence of the Guided Inquiry Learning Model Incorporating Tri Pramana on Students’ Scientific Attitudes and Understanding of Science Concepts at SMP - I Gede Someada; I Made Sedana; Ni Nyoman Lisna Handayani (Universitas Pendidikan Ganesha, 2025)
The low level of students’ scientific attitudes and conceptual understanding in science indicates that learning practices are still dominated by teacher-centered approaches and provide limited opportunities for active knowledge construction. In addition, the integration of local wisdom values into science learning has not been optimally utilized to strengthen meaningful learning and students’ scientific character development. This study aimed to analyze and examine the effect of a guided inquiry learning model integrated with Tri Pramana on students’ scientific attitudes and science conceptual understanding. This study employed a quasi-experimental method using a posttest control group design. The population consisted of 345 students, with a sample of 70 students selected through random sampling techniques. Data were collected using a scientific attitude questionnaire and a science conceptual understanding test that met validity and reliability requirements. The data were analyzed using MANOVA. The results revealed a significant simultaneous effect of the Tri Pramana-based guided inquiry learning model on students’ scientific attitudes and conceptual understanding, as indicated by F = 25.156 and p < 0.05. Conceptually, these findings confirm that integrating inquiry-based learning with the epistemological framework of Tri Pramana strengthens scientific knowledge construction while fostering students’ scientific character. This model therefore has strong potential as an innovative approach to promote contextual, meaningful, and competence-oriented science learning.